2022
DOI: 10.1002/ece3.9489
|View full text |Cite
|
Sign up to set email alerts
|

Demographic history and gene flow in the peatmosses Sphagnum recurvum and Sphagnum flexuosum (Bryophyta: Sphagnaceae)

Abstract: Population size changes and gene flow are processes that can have significant impacts on evolution. The aim of this study was to investigate the relationship of geography to patterns of gene flow and population size changes in a pair of closely related Sphagnum (peatmoss) species: S. recurvum and S. flexuosum . Both species occur in eastern North America, and S. flexuosum also occurs in Europe. Genetic data from restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Higher levels of genetic diversity in ENA also support this hypothesis. Studies of amphi‐Atlantic S. flexuosum (Imwattana et al, 2022) and S. angermanicum (Stenøien et al, 2011) showed similar patterns of lower European diversity. In S. capillifolium , S. fuscum , and S. warnstorfii plants from ENA versus Europe did not form reciprocally monophyletic clades (Appendices S2, S3), and there could be multiple origins of the amphi‐Atlantic patterns and/or the phylogenetic signals have been erased by intercontinental gene flow.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Higher levels of genetic diversity in ENA also support this hypothesis. Studies of amphi‐Atlantic S. flexuosum (Imwattana et al, 2022) and S. angermanicum (Stenøien et al, 2011) showed similar patterns of lower European diversity. In S. capillifolium , S. fuscum , and S. warnstorfii plants from ENA versus Europe did not form reciprocally monophyletic clades (Appendices S2, S3), and there could be multiple origins of the amphi‐Atlantic patterns and/or the phylogenetic signals have been erased by intercontinental gene flow.…”
Section: Discussionmentioning
confidence: 88%
“…A comparison of genetic diversity between ENA and European plants of S. flexuosum (subg. Cuspidata; Imwattana et al, 2022) similarly revealed less genetic diversity in Europe.…”
Section: Discussionmentioning
confidence: 96%